Liking Harm, Feeling Fine: Crowd-Cruelty Comfort and the Normalization of Digital Aggression - Sulejmanović, Dijana; Kadić, Irma (NBP. Nauka, bezbednosti, policija, 2025)
This article explores the psychological processes and behavioral practices that result from an individual’s involvement in online aggression, with a particular focus on social reinforcement processes in virtual communities. Theoretical frameworks well-grounded in the psychological literature, such as deindividuation, moral distancing, and digital disinhibition, will help identify general characteristics of online aggressors and specific behaviors such as endorsing the group through likes, shares, and supportive comments. In an effort to capture the complexity of the online space, an innovative and explanatory concept called Crowd-Cruelty Comfort (CCC) is presented - as a new theoretical framework that describes how individuals have reduced moral discomfort and increased psychological comfort when engaging in harmful or supportive behaviors in the digital space. This concept explains the growing normalization of online aggression through well-studied concepts and mechanisms such as moral mitigation, diffusion of responsibility and suppression of empathy, which were previously identified and explained in the literature, but are now observed in a new context, with new meanings and new consequences that they leave in virtual reality. CCC describes how individuals psychologically process that the harmful or destructive behaviors they engage in are in fact morally justified—and therefore can believe they are not to blame for the behavior and can maintain a positive self-image. The implications of this concept are discussed with respect to digital ethics education, prevention strategies, and intervention programs aimed at mitigating the spread of online harm.